Importance of Chemistry Education and Methods That are Used in Teaching - Ravshanova Fotima Kamolovna (Genius Journals, 2022)
Through this article, we are going to explore important peculiarities of teaching chemistry and ways that are used in classroom. Moreover, different techniques of teaching chemistry were discussed
Keywords: Chemistry education; physical sciences; transferable skills; Laboratory courses